2014
DOI: 10.1007/s12020-014-0465-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of SIRT1 associate with non-alcoholic fatty liver disease in obese patients

Abstract: Sirtuins (SIRTs) are master metabolic regulators with protective roles against obesity and obesity-associated metabolic disorders, including non-alcoholic fatty liver disease (NAFLD) and type-2 diabetes. We aimed to ascertain whether there is a relationship between serum SIRT1 and liver steatosis severity in obese patients. Seventy-two obese patients (BMI ≥ 30 kg/m(2)), 18 males and 54 females, mean age 39.66 ± 12.34 years, with ultrasonographic evidence of NAFLD, were studied. BMI, transaminases, insulin, HOM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 41 publications
2
75
0
Order By: Relevance
“…Deng et al [41] reported a reduction of SIRT1 expression in rats with NAFLD induced by high-fat diets. In addition, Mariani et al [42] observed that SIRT1 expression was significantly decreased in visceral adipose tissue of morbidly obese patients with severe steatosis, compared to patients with slight or moderate steatosis. Remarkably, the molecular mechanisms of the action of taurine in correction of NAFLD was reported in the study of Banks et al [43], who explained that taurine increases the expression of SIRT1 in the liver which further stimulates the antioxidant capacity, by SOD induction and lowering the proinflammatory signals, TNF-α and interleukin 6 (IL-6).…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al [41] reported a reduction of SIRT1 expression in rats with NAFLD induced by high-fat diets. In addition, Mariani et al [42] observed that SIRT1 expression was significantly decreased in visceral adipose tissue of morbidly obese patients with severe steatosis, compared to patients with slight or moderate steatosis. Remarkably, the molecular mechanisms of the action of taurine in correction of NAFLD was reported in the study of Banks et al [43], who explained that taurine increases the expression of SIRT1 in the liver which further stimulates the antioxidant capacity, by SOD induction and lowering the proinflammatory signals, TNF-α and interleukin 6 (IL-6).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown a correlation between plasma SIRT1 and NAFLD in obese patients. SIRT1 levels were found to be significantly lower in an obese group with severe liver steatosis compared with a group with mild steatosis, and both groups had lower levels in the plasma compared with control lean patients [15,16]. It has long been known that obesity and NAFLD lead to ER stress and the UPR [17].…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics make SIRT1 a potent regulator of lifespan, metabolism and stress responses (Haigis & Sinclair, 2010;Houtkooper et al 2012). Both ageing and obesity negatively affect SIRT1 expression and activity (Pedersen et al 2008;dos Santos Costa et al 2010;Mariani et al 2015). Conversely, overexpression of SIRT1 mimics caloric restriction (Wood et al 2004), leading to a longer lifespan and resistance to obesity-related disorders in various animal models (Wood et al 2004;Milne et al 2007;Pfluger et al 2008).…”
Section: Introductionmentioning
confidence: 99%